The Physicochemical and Sensorial Characteristics of Plant-based Patty Formulated with Oyster Mushroom and Rubber Seed Flour (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
An increasing trend toward a meat-free diet is observed nowadays, as health-conscious consumers tend to limit their use of animal products due to the known association between high meat consumption and overweight, obesity, and an increased risk of chronic diseases. Rubber seed is an underutilised ingredient with a high protein content and has potential for use in the development of plant-based food products. Oyster mushrooms are low in fat and cholesterol and have an umami flavour that provides a taste similar to that of meat. Thus, this study was designed to explore the potential use of oyster mushrooms and rubber seeds as meat replacers for the development of a patty. The sensory and physicochemical features of plant-based patties with varying quantities of rubber seed flour (RSF) and oyster mushroom (OM) were determined. Sensory examination found that products containing 15% RSF were highly accepted by the panellists when compared to the other samples. The addition of RSF resulted in a substantial (p
Keywords: Meat Analogues; Sustainable Ingredients; Plant Protein; Texture; Sensorial Properties